A sociolinguistic exploration of cultural diversity in the translation of street food names in Malaysia from Chinese to English - Zhu, Hongxiang (2024)
The research problem that is to be addressed in this study revolves around the challenge of inconsistency in the non-professional translations of street food names by food vendors. Drawing on a sociolinguistic approach, this study aims: (1) to identify the cultural elements in Chinese street food names in Malaysia; (2) to examine the translation techniques on the street food names in Malaysia from Chinese to English; and (3) to explore the reflection of cultural diversity in the translation of street food names in Malaysia from Chinese to English. This study is a qualitative case study in which the translation of Chinese street food names in Malaysia is the case. Chinese street food names refer to street foods eaten by Chinese Malaysians. The research settings cover Penang, Perak, Perlis, Johor, Kedah, Malacca, Negeri Sembilan, Sarawak, Sabah, Selangor, and Kuala Lumpur. A purposive sampling method is employed to collect street food names in Malaysia. The sampling size is 4,214 name pairs with translation, including 2,199 noodle foods, 711 rice foods, and 1,304 others. Ng et al.’s (2015) category of food nomenclature is adopted to identify the cultural elements and Marco’s (2019) model of translation techniques are used to examine how these street food names are translated. The diverse cultures in translation are explored based on the pronunciations of elements in translated street food names and the geographical names in translation that can mark the origins of the foods. The findings of the analysis revealed that: (1) the cultural elements are identified based on ingredient, cooking method, food attribute, commemorative aspects, good names and their combinations; (2) the translation techniques—borrowing, literal translation, neutralisation, amplification, intracultural adaptation, intercultural adaptation, and omission— are used; and (3) the diverse cultures are reflected by amplification and literal translation of commemorative aspects—especially geographical names and national names—borrowing of the cultural elements based on regional pronunciation and intracultural adaptation of using elements of third cultures.